2010
DOI: 10.1016/j.freeradbiomed.2010.02.033
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PKcs deficiency leads to persistence of oxidatively induced clustered DNA lesions in human tumor cells

Abstract: DNA-dependent protein kinase (DNA-PK) is a key non-homologous end joining (NHEJ) nuclear serine/threonine protein kinase involved in various DNA metabolic and damage signaling pathways contributing to the maintenance of genomic stability and prevention of cancer. In order to examine the role of DNA-PK in processing of non-DSB clustered DNA damage, we have used three different models of DNA-PK deficiency i.e. chemical inactivation of its kinase activity by novel inhibitors IC86621 and NU7026, knock-down and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 57 publications
2
31
0
3
Order By: Relevance
“…The inaccurate repair of such "hybrid clusters", consisting of DSBs and non-DSBs, can be attributed to the error-prone DNA repair pathways implicated in this case like NHEJ and its backup subpathways alt-EJ (or B-NHEJ) and BER, respectively [7,8,37]. Previous studies by Peddi et al [57] have shown, using an adaptation of PFGE and different types and levels of DNA-PK deficiency, that these deficient cells not only exhibit as expected DSB repair problems, but also the non-DSB oxidative clustered DNA lesions processing is significantly impeded. Therefore, these repair resistant DSB sites (foci) will be expected to carry a heavy load of non-DSB damage increasing the possibility for misrepair and chromosomal breaks [50].…”
Section: Discussionmentioning
confidence: 95%
“…The inaccurate repair of such "hybrid clusters", consisting of DSBs and non-DSBs, can be attributed to the error-prone DNA repair pathways implicated in this case like NHEJ and its backup subpathways alt-EJ (or B-NHEJ) and BER, respectively [7,8,37]. Previous studies by Peddi et al [57] have shown, using an adaptation of PFGE and different types and levels of DNA-PK deficiency, that these deficient cells not only exhibit as expected DSB repair problems, but also the non-DSB oxidative clustered DNA lesions processing is significantly impeded. Therefore, these repair resistant DSB sites (foci) will be expected to carry a heavy load of non-DSB damage increasing the possibility for misrepair and chromosomal breaks [50].…”
Section: Discussionmentioning
confidence: 95%
“…1B). The peptides were each incubated with active RSK2 and [g- 32 P]ATP in an in vitro kinase assay. The results showed that Ser16 was consistently and strongly phosphorylated by RSK2 (Fig.…”
Section: Rsk2 Phosphorylates Histone H2ax In Vitromentioning
confidence: 99%
“…Members of the phosphatidylinositol-3 (PI-3) kinase family, including ATM, ATR, and DNA-PK, also regulate histone H2AX phosphorylation and are known to be involved in the DNA damage response induced by replication stress (9, 12, 14, 15). DNA-PK responds to oxidative stress as well in human tumor cell lines (32), and phosphorylation of H2AX at Ser139 is induced in lymphocytes after oxidative stress (33). To determine the role of these kinases in EGF-induced H2AX phosphorylation, we treated cells with the PI-3 kinase family inhibitor, wortmannin (5, 34), for 1 hour before EGF treatment.…”
Section: Dna-pk But Not Atm or Atr Is Involved In Egf-induced Phospmentioning
confidence: 99%
“…Depletion of DNA-PKcs through shRNA transfection resulted in inhibition of cell proliferation and increased apoptosis in human cervical cancer HeLa cell line exposed to cisplatin [33]. Moreover, besides the capability of the non-homologous-end-joining repair for DNA double strands breaks (DSBs), DNA-dependent protein kinase (DNA-PK) is involved in processing the oxidatively induced non-DSB clustered DNA lesions, which is important for the therapeutic efficiency of cancer treatments based on the induction of oxidative stress [34]. Mutant forms of DNA-PKcs at serine/threonine residues in the 2,609-2,647 cluster or specific inhibitor KU57788 could completely block or markedly reduce the efficiency of end joining [35].…”
Section: Discussionmentioning
confidence: 99%